Bienestar: ¿una experiencia subjetiva? - Quinteros Zúñiga, Dámaris (2019)
This paper is a literature review and aims compression human welfare as a positive experience, through the lens of abiblical worldview and the spirit of prophecy. Model is extracted based on the biblical premise divine interest in thewelfare of human being (Jer. 29:11, Psalm 35:27), and the need to understand and practice God’s law as a conditionfor the enjoyment of a genuine welfare (Job: 36:10, Proverbs 3:2). They comprise two temporal dimensions in thewellness experience, the earthly and the eternal (Ps. 25:13, HC, 275, HAp, 280), plus 4 areas: physical, mental,social and spiritual that feed them. Development agents and designed well, are in the home, in schools, hospitalsor other Christian and church. From this perspective we analyze the contributions found in scientific psychologicalliterature on this subject, being conceived as a subjective, global positive and life that endures over time (Diener,1994). Also, through various studies, it highlights the importance of this construct as correlates and impact on anumber of important physiological processes, such as assertiveness and academic performance, resilience, optimismand happiness, among others. We conclude that the study of well-being is important for the nuclear role it playsin human existence that transcends the subjectivity of who experiences it. From the biblical concept of welfare iscultivating a relationship with the Creator and the observance of the divine laws, which generates thoughts, attitudesand positive behaviors. Only in this way every man and woman can enjoy a full well-being in all its dimensions. Inaddition to the well-being experienced in earthly life the principles of God are a prelude to the true eternal welfarewhich should endeavor.